The Role of Subcutaneous Fat Composition on Blood Pressure: A Study on Students Aged 15-18 at Kalam Kudus II Senior High School Jakarta, Indonesia - Marendra Shinery Kartolo; Santoso, Alexander Halim; Yohanes Firmansyah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Hypertension is one of the leading causes of death worldwide. There was an increase in the prevalence of hypertension in children and adolescents ≤19 years of age from 2000 to 2015. Body mass index (BMI) and subcutaneous fat distribution are linked to blood pressure variations. Methods: The cross-sectional study was carried out at Kalam Kudus II Senior High School Jakarta from June – August 2023. The inclusion criteria in this study included students of Kalam Kudus II Senior High School Jakarta, aged 15-18 years, registered as active students at the time the study was conducted, physically and spiritually healthy, and willing to participate in the study. The exclusion criteria for this study include students who refused participation, did not obtain permission from their parents, or students with medical disorders that affect anthropometric results and blood pressure. Data was taken from direct measurement and performed multivariate testing using the double linear regression test enter method in SPSS. The statistical significance is 0.05. Results: An analysis of 102 students found that only BMI had a significant relationship with systolic blood pressure, and no anthropometric variable had a meaningful relationship with diastolic pressure. Conclusion: There are many ways and factors for measuring body composition. It is important to test the body composition and BMI of adolescents to reduce the risk of hypertension later in the day.